Hierarchy of principles in islamic management: A literature review of philosophical, normative, and applicative approaches - Roidah lina; Putri Ana Nurani (At Turots: Jurnal Pendidikan Islam, 2025)
Islamic management is a value system approach that combines spiritual, ethical, and professional aspects in organizational management. This research aims to formulate a hierarchical model of Islamic management principles that includes philosophical, normative, and applicative dimensions. The method used is a systematic literature review (SLR) with thematic analysis of Islamic and academic literature. The results of the research produced a five-level hierarchical model that includes philosophical dimensions (monotheism, the law of Allah), strategic (justice, leadership), process (deliberation, balance), relational (human relations), and operational (transparency, responsibility, service). This finding presents an integral and contextual conceptual framework as a sharia-based managerial alternative. This model also has the potential to be used as a reference in Islamic institutional practices that are oriented towards values and benefits